A conceptual paper on subjective poverty as perceived lasting socioeconomic insecurity among low income household during MCO and COVID 19 pandemic / Azhana Othman - Othman, Azhana (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
Studies into the relation between subjective perceptions of individuals and objective economic conditions have usually resulted in ambiguous empirical findings. Whilst most studies perceive subjective welfare as being operationalized by indicators of happiness or life satisfaction, this study narrow the approach to an economic domain of subjective, that is perceptions of poverty. Malaysia government is very committed in supporting and implementing the 2030 Agenda for Sustainable Development and its 17 Sustainable Development Goals (SDGs). Having reduced absolute poverty to less than one per cent, Malaysia is now focusing on uplifting the quality of life of the bottom 40 per cent of households (B40). Nevertheless, the implementation of the Movement Control Order (MCO) and the COVID-19 outbreaks have affected the financial 'immunity' of households, traders, and employers to survive this critical period. This made many feels poorer. Poverty rates in the country have been found to increase as many Malaysians easily fall into poverty after losing their jobs or having their pay cut due to the Covid-19 pandemic. Recently, economist adding the subjective poverty approach in understanding the poor. Poor people have their own understanding and interpretation of their social certainty, and this is often different to an outsider's perspective. The paper aims to uncover subjective poverty as perceived lasting socioeconomic insecurity among the low-income household.